2021
DOI: 10.1080/00365513.2020.1864833
|View full text |Cite
|
Sign up to set email alerts
|

Reference intervals for 12 clinical laboratory tests in a Danish population: The Lolland-Falster Health Study

Abstract: Reference intervals (RIs), developed as part of the Nordic Reference Interval Project 2000 (NORIP) are widely used in most European laboratories. We aimed to examine the validity of the NORIP RIs by establishing RIs for 12 frequently used laboratory tests based on data from a local Danish population and compare these local RIs with the NORIP RIs. Using an a posteriori direct sampling approach, blood sample data were assessed from 11,138 participants aged 18þ years in the Lolland-Falster Health Study (LOFUS), o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
1
2
0
Order By: Relevance
“…The main findings included the facts that RIs for serum TP and ALB didn't require gender partitioning, which was consistent with national standard, Canada and Denmark (23,24). The downward tendency in serum TP concentrations may be due to the decrease in the volume and number of liver cells with age.…”
Section: Age-specific Distributions Of Liver Function Tests In the El...supporting
confidence: 56%
See 1 more Smart Citation
“…The main findings included the facts that RIs for serum TP and ALB didn't require gender partitioning, which was consistent with national standard, Canada and Denmark (23,24). The downward tendency in serum TP concentrations may be due to the decrease in the volume and number of liver cells with age.…”
Section: Age-specific Distributions Of Liver Function Tests In the El...supporting
confidence: 56%
“…The Supplemental table lists the RIs obtained in this study and RIs derived from national standards (20)(21)(22). Studies in Canada, Denmark and Asmara, Eritrea were also used to compare the differences in RIs among regions (23)(24)(25). The relative deviations of the LL and UL of each analyte's RIs with the national standard and other studies were also included.…”
Section: Establishment Of Ris In Northeast China and Comparison With ...mentioning
confidence: 99%
“…Although the effect of sex, age, and body mass index (BMI) on specific biomarkers has been examined in large studies 4 – 6 , these studies have reported on the presence of associations between biomarkers and various traits and not on absolute biomarker concentrations in specific subgroups. Further, studies with concentration levels for reference and comparison are relatively limited in sample sizes 7 9 , or only include limited numbers of biomarkers (<30) 10 12 . Consequently, information on expectable concentrations is scarce for plasma concentrations of biomarkers stratified by sex, age, BMI, and common lifestyle factors such as smoking, i.e., phenotypes that are not exclusive to the criteria defining a healthy individual.…”
Section: Introductionmentioning
confidence: 99%